Using Propensity Score Matching to Evaluate Differences in Public and Private Students on Self-Control - Matthew Hanauer (International Journal of School Social Work, 2019)
With the Educational Childhood Longitudinal Kindergarten Cohort class of 2011 (ECLSK-2011) database, I used propensity score matching and a longitudinal multilevel model to evaluate how 4970 kindergarteners in public (assigned public, charter, or magnet) and private (religious, non-religious private) schools, who were matched on a host of covariates, differed on a psychometrically sound self-control construct from fall 2010 to spring 2012. I found no statistically significant difference in self-control scores between private and public-school children. I discuss possible more effective and equitable mechanisms for improving student self-control, as well as suggesting guidance for future research on this topic.
Keywords: propensity score matching; social and emotional learning; private schools; school social workers